Magnetic properties, adhesive characteristics, and optical properties of Co40Fe40W20 films. (3rd April 2021) - Liu, Wen-Jen; Ou, Sin-Liang; Chang, Yung-Huang; Chen, Yuan-Tsung; Liang, You-Cheng; Chang, Chun-Yu; Chu, Chun-Lin; Wu, Te-Ho
ABSTRACT: X-ray diffraction patterns demonstrated a significant nanocrystalline body-centred cubic CoFe (110) structure when the thickness was between 60 and 90 nm, and displayed an amorphous status when the thickness was from 18 to 42 nm. The saturation magnetization ( Ms ) and low-frequency alternate-current magnetic susceptibility ( χ ac ) revealed a thickness effect owing to the nano-magneto crystalline anisotropy. The Hc value was smaller than 2 Oe due to the small grain size distribution. The increased surface roughness could induce a greater pinning effect of the domain wall. The 90-mm thickness had the highest χ ac 0.27 value at an optimal resonance frequency ( f res ) of 100 Hz. The highest surface energy was 44.72 mJ/mm 2 at 42 nm and demonstrated high adhesion. The transmittance decreased from 13.1% to 0.27% because the thicker thickness and interface effects inhibited the transfer of photon signals to the film, resulting in a low transmittance and high absorbance.